1997
DOI: 10.1016/s0954-6111(97)90005-6
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in patients under long-term oxygen therapy: a home-based descriptive study

Abstract: Long-term home oxygen therapy (LTOT) improves survival of hypoxic patients with chronic respiratory insufficiency. However, the health-related quality of life (HRQL) of these patients, when LTOT is initiated, is severely impaired. The present study aims to describe the health-related quality of life (HRQL) of patients under LTOT, assessed at home, to identify parameters relevant to HRQL, and to describe changes over a 1-yr period. Seventy-nine patients (aged 68 +/- 11 years, under LTOT for 34 +/- 24 months) un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 32 publications
0
13
1
5
Order By: Relevance
“…Variations in the levels of anxiety in patients with COPD have been reported in 21% to 96% of the cases. (18,19) Half of our patients had depression. Other authors have found rates between 27% and 79%.…”
Section: Resultsmentioning
confidence: 82%
“…Variations in the levels of anxiety in patients with COPD have been reported in 21% to 96% of the cases. (18,19) Half of our patients had depression. Other authors have found rates between 27% and 79%.…”
Section: Resultsmentioning
confidence: 82%
“…Janssens and colleagues [28] found an improvement in the quality of life of 79 subjects by the SGRQ they applied at the beginning and end of the first year. In the NOTT study, there was an improvement in the neuropsychological functions and qual-ity of life of the group receiving continuous oxygen treatment; however quality of life was not evaluated by the SGRQ [4].…”
Section: Subjectsmentioning
confidence: 99%
“…Studies have shown that patients present weight loss, and a loss of lean body mass resulting in peripheral muscle dysfunction, decreased muscle strength, exercise tolerance, with a reduction in muscle strength proportional to the reduction in muscle mass (4,5,6), in addition to respiratory muscle weakness (7).…”
Section: Introductionmentioning
confidence: 99%